Judaism and its Bible: a people and their book - Greenspahn, Frederick E. (Jewish Publication Society, 2023)
Judaism and Its Bible explores the profoundly deep yet complex relationship between Jews, Judaism, and the Hebrew Bible, describing the extraordinary two-and-a-half-millennia journey of a people and its book that has changed the world.